Oferta e distribuição de estágio supervisionado em cursos de odontologia do estado de Minas Gerais, Brasil - Soares Francisco, Kleryson Martins [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Diniz, Diego Garcia [UNESP]; Saliba, Nemre Adas [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
Since 2002, which are in effect the Curriculum Guidelines for National Graduate courses in dentistry. The adequacy of the education needs of the Unified Health System is one of its main goals. As guidance, a way of achieving this goal is through supervised, which are presented as a tool for improving the academic scientific and technical, providing you know the reality of health and society in which to work. This study aims to examine the supply and distribution of supervised in graduate programs in dentistry in the state of Minas Gerais - Brazil. The material for analysis was obtained by sending letters to courses and consulting to its sites on the Internet. Were part of the study, 15 of the 23 courses in the state. It appeared that the load-hours of supervised showed variations between 315 and 975 hours, with only 20% of courses devoted 20% of the total working hours of supervised practice. There was no correlation between the total working hours of the course and working hours of supervised practice. The courses in which the supervised activities were represented only by extra muros showed a lower percentage of working hours in relation to total working hours of the course.

Desde 2002 encontram-se em vigência as Diretrizes Curriculares Nacionais dos Cursos de Graduação em Odontologia com o propósito adequar o ensino às necessidades do Sistema Único de Saúde. Uma das formas de atingir essas metas, conforme orientação é através dos Estágios Supervisionados, os quais se apresentam como instrumento para o aperfeiçoamento científico e técnico do acadêmico, proporcionando-o conhecer a realidade da saúde e da sociedade na qual irá trabalhar. Este estudo tem como objetivo analisar a oferta e distribuição do Estágio Supervisionado nos cursos de graduação em Odontologia do estado de Minas Gerais - Brasil. O material para análise foi obtido através do envio de ofícios aos cursos e da consulta aos seus sítios na internet. Fizeram parte do estudo, 15 dos 23 cursos do estado. Constatou-se que as cargas- horárias dos Estágios Supervisionados apresentaram variações entre 315 e 975 horas, sendo que apenas 20% dos cursos dedicam 20% da carga horária total aos Estágios Supervisionados. . Não foi encontrada correlação entre a carga horária total do curso e a carga horária do Estágio Supervisionado. Os cursos os quais os Estágios Supervisionados eram representados somente por atividades extramurais apresentaram menor porcentagem de carga horária com relação à carga horária total do curso.
Supply and distribution of supervised in dentistry courses from state of Minas Gerais, Brazil
Keywords: Schools; Dental; Education; Dental; Dentistry